Utilização da cinza do bagaço da cana-de-açúcar como agregado miúdo em concretos para artefatos de infraestrutura urbana - Bessa, Sofia Araújo Lima (2011)
Brazil is the main sugarcane world-producer and it is the leader in all segments (sugarcane, sugar and alcohol). The waste consisting of sugarcane bagasse is produced at the end of grinding process and it is used to generate energy through burning in boilers. At the end of burning, the ashes of bagasse are often thrown into environment improperly. In this context, the Construction Industry is a sector in which the incorporation of a couple of wastes is propitious, whereas applications of construction materials properties are considered. This research is justified by the need of assess the possibility of use of sugarcane bagasse ash in construction products, especially given its large volume. Used like raw material, the waste would no longer be the primary cause of problems related to public health and the environment. The goal of this research was to analyze the sugarcane bagasse ash (SBA) as a substitute for fine aggregate in concretes and mortars directed to the production of artifacts for the urban infrastructure. The SBA samples were collected in sugar and alcohol mills in the state of São Paulo and, then, they were characterized by physical and chemical tests. The SBA was used in cement mortars with 0%, 10%, 20%, 30%, 50% and 100% substitution levels. After the mechanical tests, the 30% and 50% levels of SBA were chosen for the study and production of concretes, which were evaluated through dosage studies, mechanical and durability tests, and economical and environment studies for SBA like a substitution of sand. The artifact chosen for analysis was a concrete curb (dimensions 1,00 x 0,15 x 0,30 m) that was used for drainage and pavement of pathways. Regarding the results obtained, the concrete produced with the SBA and cement CP II E 32 (Group C) had the best mechanical results compared to their respective reference series. Regarding durability, it is possible to say that the use of ash as a partial replacement of sand does not affect the service life of concrete artifacts. It can be also concluded that despite the use of the SBA did not diminish significantly the final value of m3 of concrete, the gain in relation to mechanical performance was higher. On the analysis of the artifact, it can be concluded that the guides produced in this research had sufficient mechanical strength to be demolded, transported and stored before use in the same way that guides conventional precast pavement.